Pengaruh Literasi Keuangan dan Layanan Fintech terhadap Perilaku Manajemen Keuangan Mahasiswa Pendidikan Ekonomi di Universitas PGRI Wiranegara - Auliya Ristiani; Sugeng Pradikto (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze how financial literacy and the frequency of use of financial technology (fintech) services affect the financial management patterns of students in the Economics Education Study Program at Universitas PGRI Wiranegara. The digitalization era has changed the way students manage their finances, which now combine traditional financial understanding with the implementation of digital technology innovations. This research uses a quantitative method with an explanatory approach, involving respondents selected through random stratification to ensure balanced representation. Data collection uses a Likert scale questionnaire instrument, while data analysis applies a multiple linear regression model. Empirical results prove that financial literacy and fintech utilization both have a significant and positive impact on students' financial management patterns. Together, these two factors can explain most of the variation in respondents' financial behavior. These findings emphasize the importance of integrating fundamental financial knowledge with the ability to adapt to digital technology as a foundation for forming effective financial management competencies in the modern era. In terms of implementation, the results of this study suggest strengthening the economics education curriculum that includes learning digital financial literacy and the use of fintech services that are wise and ethical.